Socio-economic status of crab collectors and fatteners in the southwest region of Bangladesh (Journal of the Bangladesh Agricultural University, 2010)
The study was conducted to assess the socio-economic conditions of mud crab (Scylla serrata) collectors and fatteners in Khulna and Satkhira districts. From January to June 2009, 40 crab collectors and 40 crab fatteners were considered where 45% of the crab collectors collected crabs from the Sundarban and fattening of mud crabs were generally done in bamboo cages and in ponds. Data analyses revealed that most of the crab collectors and fatteners were Hindus and few were Muslims. In the study area, 40% and 55% crab collectors and fatteners respectively were from the age group of 31-40 years. The crab collectors (80%) had above 6-10 members in their family and 55% of the crab fatteners had above 6-10 members. There were 45% of the crab fatteners had 151 decimal and above land, but 35% of the crab collectors had 0-50 decimal which was very small. Annual income of the crab collectors was less than Tk.90,000, where the lowest annual income of the crab fatteners was Tk. 90,000-150,000. Natural disasters and other constraints affected the livelihood of crab collectors and fatteners in the southwest region. So, crab collection and fattening are alternative sources of income and sustainable livelihood for the disadvantaged people in the southwest Bangladesh. Keywords: Crab collectors; Crab fatteners; Socio-economic conditions; Southwest Bangladesh DOI: 10.3329/jbau.v7i2.4754 J. Bangladesh Agril. Univ. 7(2): 411-419, 2009